ANALISIS KEADILAN RESTORATIF KEJAKSAAN DITINJAU DARI ASAS KEPASTIAN HUKUM - Ndruru, Grace; Mardian Putra Frans (The Juris, 2024)
This research aims to analyze the process of peace efforts based on restorative justice in the prosecutor's office which only stops at issuing a decree to terminate the prosecution. implementation of restorative justice implemented by the prosecutor's office which has not been able to comply with the principle of legal certainty. So far, the process of seeking peace at the prosecutor's office only stops with a letter of decision to terminate the prosecution, in which the representation of the prosecutor's office as a peacemaker only targets peace between the suspect and the victim. in other words, there is no target for fulfilling the responsibilities that should be given to victims. Legal certainty is a guarantee of certainty that the law is running well without any arbitrary action, which means that rights and obligations are fulfilled. If legal certainty is achieved then each party gets the same rights. This research uses a normative juridical method with a statutory regulatory approach and a conceptual approach. The results of this research explain that case resolution based on restorative justice in the prosecutor's office between perpetrators, victims and the prosecutor's office itself has not been able to fulfill the principle of legal certainty. This is because the prosecutor's efforts and pursuit are only to achieve peace, without considering the aspects of responsibility that must be fulfilled by the parties involved and bound. In the sense that Prosecutor's Regulation Number 15 of 2020 does not fulfill the principle of legal certainty.